Integration of Brain Activity, Neurophysiology and Neuromechanics In Cycling Performance: A Conceptual Framework - Nurul Farha, Zainuddin (Kementerian Pendidikan Tinggi (KPT), Malaysia, 2019)
Link to publisher's homepage at http://www.mohejournal.com/index.php/mohe